Does a high sowing density of common bean change the weed interference periods? - Tejada, Jorge Luis [UNESP]; Lemos, Leandro Borges [UNESP]; Alves, Pedro Luis da Costa Aguiar [UNESP] (Univ Federal Rural Pernambuco, 2022)
In order to determine the effect of sowing density on weed interference in common bean, two experiments were carried out in Jaboticabal municipality in 2020: one with 15 (FPM) and other with 10 bean plants m-1 (TPM). The treatments were periods of control and coexistence: 0-10, 0-20, 0-30, 0-40, 0-50, 0-60, and 0-80 days after emergence (DAE), totaling 14 treatments, in four replications, under a randomized block design. Was carried out a phytosociological analysis of the weeds and the regression of their dry mass with productivity. Nonlinear regression analysis of productivity was performed to determine the period before interference (PBI), critical period for interference prevention (CPIP) and total period interference prevention (TPIP). The predominant species were: Nicandra physaloides, Digitaria nuda, and Brachiaria plantaginea. CPIP in FPM showed a reduction in four days and PBI had an increase of 7 DAE, compared to TPM. The accumulation of weed dry mass exponentially decreased crop productivity, this decrease being greater in FPM compared to TPM. The higher sowing density gave the culture greater competitive capacity over some weed species.
Keywords: cultural weed control; Phaseolus vulgaris L; plant density